Salivary gland function and redox status in young adult male rats treated with the psychostimulant short-release methylphenidate - de Lima, José Vitor Furuya [UNESP]; Lopes, Lauani Murakami [UNESP]; Barzotti, Renan José [UNESP]; Sampaio, Larissa Victorino [UNESP]; Vazão, Arieli Raymundo [UNESP]; de Freitas, Rayara Nogueira [UNESP]; Dos Santos, Harim Tavares; Lima, Rafael Rodrigues; Chaves Neto, Antonio Hernandes [UNESP] (Springer Nature, 2025)
This study evaluated the salivary flow rate, biochemical composition of saliva, and redox status of the salivary glands in rats treated with short-release methylphenidate hydrochloride (MPH), a psychostimulant commonly used in the treatment of attention deficit hyperactivity disorder. Twenty young adult male Wistar rats (6 weeks old) were randomly assigned to two groups (n = 10): Control (0.9% saline) and MPH (3 mg/kg). After 28 consecutive days of intragastric gavage, saliva was collected following pilocarpine stimulation, for analysis of salivary flow rate (mL/min/g of salivary gland), pH, buffering capacity, and biochemical composition. Redox status markers were also assessed in the parotid and submandibular glands. The results showed that MPH treatment reduced salivary flow rate and buffering capacity without altering pH. Increases in total protein concentration, amylase activity, and concentrations of calcium and phosphate were observed, with no significant differences in sodium, potassium, or chloride content. MPH also decreased total oxidant capacity and the activities of superoxide dismutase and catalase in both salivary glands. Interestingly, oxidative damage to lipids and proteins was lower in the MPH group for the parotid glands. On the other hand, MPH reduced total antioxidant capacity and glutathione peroxidase activity in the submandibular glands, while it did not alter uric acid and reduced glutathione concentrations in either gland. In summary, MPH reduced salivary flow, altered the salivary biochemical composition, and disrupted redox homeostasis in the salivary glands. These salivary biochemical alterations may corroborate the reduction in salivary flow and contribute to oral health deterioration associated with methylphenidate use.